PARTISIPASI MASYARAKAT DALAM PEMELIHARAAN KESEHATAN LINGKUNGAN PERMUKIMAN DI KECAMATAN PAUH DUO KABUPATEN SOLOK SELATAN - azmi julia indra; afdhal afdhal (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
This study aims to determine community participation in the maintenance of residential environmental health in Pauh Duo Subdistrict, seen from the management of house hygiene, clean water management and waste and household waste management. This type of research is quantitative descriptive. The study population was all family heads who were or residing in the Pauh Duo sub-district of South Solok Regency which numbered 4,985 heads of families. The research sample was taken by the method of